Identification of factors relating to the development of ball speed and one-legged landing in the volleyball attack - Vint, P. F.
Success in spiking or attacking is directly related to team success in volleyball. Although little is known about the biomechanics of the volleyball attack, it can be argued that the development of ball speed is one of the primary factors that contribute to successful attacking. The harder the ball is attacked, the faster the ball will travel and the shorter the time opposing defenders will have to successfully keep the ball in play. As such, an understanding of the mechanical factors that contribute to the development of ball speed during the attack is of great interest to volleyball coaches and athletes.